Antara Dunia Nyata dan Virtual: Studi Kasus Remaja dengan Gangguan Kesehatan Mental Akibat Kecanduan Gadget: Penelitian - Selian, Sri Nurhayati; Setianingsih, Endang; Rahma, Lisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the impact of gadget addiction on adolescent mental health, focusing on real-world and virtual interactions. A qualitative case study approach involved two male adolescents aged 16–18 years who experienced symptoms of gadget addiction and two parents as supporting informants. Data were collected through interviews, observations, and document analysis, then thematically analyzed to identify usage patterns, psychological impacts, and contributing factors to dependency. Results indicate that respondents used gadgets 10–14 hours per day for online gaming and social media, primarily as an escape from family problems and academic pressures. Impacts include social anxiety, decreased emotional regulation, sleep disturbances, and identity dissociation. Environmental factors such as family conflict, lack of supervision, and addictive technology design exacerbate the condition. The findings confirm that excessive gadget use reduces real-world social interactions and hinders psychosocial development through avoidance coping and the search for digital validation. The study recommends holistic interventions such as cognitive-behavioral therapy, emotional digital literacy, and family environmental modifications, with implications for school-based prevention programs and more responsible technology design policies.